Conceptual design of a polarized 3He neutron spin filter for polarized neutron spectrometer POLANO at J-PARC. (April 2016) - Ino, T; Ohoyama, K; Yokoo, T; Itoh, S; Ohkawara, M; Kira, H; Hayashida, H; Sakai, K; Hiroi, K; Oku, T; Kakurai, K; Chang, L J
Abstract: A 3 He neutron spin filter (NSF) has been designed for a new polarized neutron chopper spectrometer called the Polarization Analysis Neutron Spectrometer with Correlation Method (POLANO) at the Materials and Life Science Experimental Facility of the Japan Proton Accelerator Research Complex. It is designed to fit in a limited space on the spectrometer as an initial neutron beam polarizer and is polarized in situ by spin exchange optical pumping. This will be the first generation 3 He NSF on POLANO, and a polarized neutron beam up to 100 meV with a diameter of 50 mm will be available for research on magnetism, hydrogen materials, and strongly correlated electron systems.